Noonan syndrome associated with hypoplastic left heart syndrome. (22nd April 2023) - Lawrence, Kendall M.; Burstein, Danielle S.; Ahrens-Nicklas, Rebecca; Gaynor, J. William; Nuri, Muhammad A.
Abstract: Noonan syndrome is an inherited disorder caused by alterations in the RAS-MAPK pathway. There have been several identified genotype–phenotype associations made with respect to congenital cardiac lesions and Noonan syndrome variants, but limited data exist regarding single ventricle disease in this population. Here, we report two patients with PTPN11 -related Noonan syndrome and hypoplastic left heart syndrome variants.